1983
DOI: 10.1083/jcb.97.4.1226
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus neural crest cell migration in an applied electrical field.

Abstract: Xenopus neural crest cells migrated toward the cathode in an applied electrical field of 10 mV/mm or greater. This behavior was observed in relatively isolated cells, as well as in groups of neural crest cells; however, the velocity of directed migration usually declined when a cell made close contact with other cells. Melanocytes with a full complement of evenly distributed melanosomes did not migrate of their own accord, but could be distorted and pulled by unpigmented neural crest cells. Incompletely differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 17 publications
6
50
0
Order By: Relevance
“…It has been suggested that threedimensional systems of voltage gradients may be coordinates for cell migration and morphogenesis (39,40), and neural crest is particularly sensitive to extracellular electrical cues (41). However, in most cases the molecular details of these events remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that threedimensional systems of voltage gradients may be coordinates for cell migration and morphogenesis (39,40), and neural crest is particularly sensitive to extracellular electrical cues (41). However, in most cases the molecular details of these events remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, the target of EFs generated in those experiments is unclear as the EF magnitudes used (0.5 mV mm −1 ) were much smaller than those required to produce a directional effect on neurons in vitro, especially mammalian neurons (Robinson and Cormie, 2007). It is known that cultured neural crest cells from Xenopus and quail respond to applied EFs as small as 7 mV mm −1 by migrating toward the negative electrode (cathode) (Gruler and Nuccitelli, 1991;Stump and Robinson, 1983), so it is possible that Schwann cells may respond similarly.…”
mentioning
confidence: 99%
“…However, another kind of transformed cells, prostate cancer cells, move cathodally (Djamgoz et al, 2001). Another neural crest derivative, melanocytes from both Xenopus and humans, has been reported to be unresponsive to applied EFs (Grahn et al, 2003;Stump and Robinson, 1983) The directional response of the Schwann cells to an EF of 3 mV mm −1 is quite robust, as the average cosine reaches 0.31 after five hours in the field. It is possible that the cells would show significant responses to smaller fields, given a longer exposure time.…”
mentioning
confidence: 99%
“…They are essential for a variety of biological events ranging from pH regulation and maintenance of cell membrane potential to tissue development and regeneration (Altizer et al, 2001;Levin, 2007). The functional significance of endogenous ion currents and physiological electric fields has been reported at different cell biological levels, including directed migration and polarity of neural crest cells in Xenopus and in Ambystoma (Stump and Robinson, 1983;Cooper and Keller, 1984), formation of electrical coupling between mesodermal cells during the development of trunk muscle cells in Ambystoma and in Xenopus (Blackshaw and Warner, 1976), and human mesenchymal stem cell differentiation (Sundelacruz et al, 2008). Bioelectric signals, either endogenous or externally induced, have been shown to function at the molecular level in a wide range of biological processes and can be used as therapeutic tools (Zhao et al, 2006;Funk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%